NanoMITe GRANT SPURS USM TO INTENSIFY RESEARCH IN MANAGING GLOBAL WARMING - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUALA LUMPUR, 13 April 2015 – The credibility of Universiti Sains Malaysia (USM) as one of the best universities in transdisciplinary research is proven yet again after being selected by the Ministry of Education Malaysia (MoE) to lead a research in dealing with environmental problems and global warming.